Glutathione Concentration in Dunaliella salina: A Growth-Phase-Dependent Study - Midori Kurahashi; Angelica Naka; Kazuhiko Enokida; Yasuhiko Morita (Microbiology Research, 2023)
The microalga Dunaliella salina can produce antioxidants such as glutathione, which is an essential and powerful regulator of major cell functions. Changes in the glutathione concentration occur due to a microalga’s response to oxidative stress, which usually occurs when cells are exposed to environmental stressors or reach senescence. This study represents one of the few examples where changes in the glutathione concentration were tracked over the entire growth cycle of an alga. We found significant differences in the glutathione concentration depending on the growth stage. During the early lag growth phase, D. salina had relatively low levels of glutathione (190–280 µmol/1012 cell), which gradually increased as it entered the log phase (280–500 µmol/1012 cell) but then decreased as it entered the stationary phase (320–370 µmol/1012 cell). We also observed that the ratio between the reduced form of glutathione (GSH) and the oxidized form (GSSG) decreased with time, probably as a result of senescence or a lack of nutrients.